O TRABALHO DE CAMPO EM GEOGRAFIA COMO INSTRUMENTO DE ENSINO: REVISITANDO A CAPITAL FEDERAL E SUAS TRANSFORMAÇÕES ESPACIAIS (Revista Contexto & Educação, 2020)
Fieldwork in Geography contributes to the improvement of students' abilities in reading and interpreting documents and geographic and / or cartographic instruments, such as maps and letters, allowing students the opportunity to combine theoretical concepts with practice. The objective of this work is to understand the importance of the fieldwork for the teaching of geography from the student perceptions of a field work carried out in Brasília / DF, with students of the Technical Course in Administration of the National Program of Integration of Basic Education with Professional Education in the Youth and Adult Education Mode - PROEJA - of the Goiano Federal Institute, Rio Verde Campus. The results of the work allowed the students to understand the formation of Brasilia, considered a park city, from four different scales: a) bucolic; b) a monumental; c) the residential; and, d) the gregarious.